2021
DOI: 10.1002/jnr.24949
|View full text |Cite
|
Sign up to set email alerts
|

Differential barcoding of opioid receptors trafficking

Abstract: Over the past several years, studies have highlighted the δ-opioid receptor (DOPr) as a promising therapeutic target for chronic pain management. While exhibiting milder undesired effects than most currently prescribed opioids, its specific agonists elicit effective analgesic responses in numerous animal models of chronic pain, including inflammatory, neuropathic, diabetic, and cancer-related pain. However, as compared with the extensively studied μ-opioid receptor, the molecular mechanisms governing its traff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 258 publications
0
8
0
Order By: Relevance
“…It has been suggested that the region-specific differences in MOPr expression levels between A112 and G112 mice might be attributed to the variation in N-glycan types and contents across the brain (Wang et al, 2012). As reported previously, N-glycosylation of GPCRs, a post-translational modification (PTM) mainly occurring in the ER and Golgi apparatus, plays an important role in the correct folding and maturation of the receptors, thereby impacting their neuronal membrane density (Goth et al, 2020;Lemos Duarte and Devi, 2020;Degrandmaison et al, 2021). Presumably due to the differential expression of glycosyltransferases throughout the mouse brain, N-glycosylation of MOPr has been shown to be variable depending on the brain areas (Matsuhashi et al, 2003;Huang et al, 2008Huang et al, , 2012.…”
Section: µ-Opioid Receptor Knock-in Mouse Linesmentioning
confidence: 87%
See 3 more Smart Citations
“…It has been suggested that the region-specific differences in MOPr expression levels between A112 and G112 mice might be attributed to the variation in N-glycan types and contents across the brain (Wang et al, 2012). As reported previously, N-glycosylation of GPCRs, a post-translational modification (PTM) mainly occurring in the ER and Golgi apparatus, plays an important role in the correct folding and maturation of the receptors, thereby impacting their neuronal membrane density (Goth et al, 2020;Lemos Duarte and Devi, 2020;Degrandmaison et al, 2021). Presumably due to the differential expression of glycosyltransferases throughout the mouse brain, N-glycosylation of MOPr has been shown to be variable depending on the brain areas (Matsuhashi et al, 2003;Huang et al, 2008Huang et al, , 2012.…”
Section: µ-Opioid Receptor Knock-in Mouse Linesmentioning
confidence: 87%
“…Interestingly, the fate of the presumed DOPr-MOPr heteromers following ligand exposure resulted in their sorting to the lysosomal compartments (Derouiche et al, 2020). As recently reviewed in Degrandmaison et al (2021), the DOPr displays several particularities regarding the regulation of its trafficking, including its preferential targeting to lysosomes following agonist-induced internalization, as opposed to most GPCRs, including MOPr and KOPr, which are typically recycled efficiently to the neuronal plasma membrane (Ko et al, 1999;Tsao and von Zastrow, 2000;Whistler et al, 2002;Tanowitz and von Zastrow, 2003;Tanowitz et al, 2008;Degrandmaison et al, 2021). Interestingly, this specific ligand-selective cointernalization and sorting of DOPr-MOPr heteromers to lysosomes thus suggests a DOPr-driven mechanism and might also represent a potential approach to fine-tune MOPr-mediated downstream signaling (Derouiche et al, 2020).…”
Section: µ-Opioid Receptor Knock-in Mouse Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts to improve the utility of opioid pain therapy have also focused on δ receptors because they may possess a better side effect profile as compared with µ receptor-directed therapies (Quirion et al, 2020). Degrandmaison et al (2021) review trafficking patterns of the δ receptor dictated by precise amino acid motifs (akin to cellular barcodes) that direct receptor transport, internalization, recycling, and degradation. This is complemented by an elegant study from Cahill et al (2020) showing that changes in δ receptor ultrastructural localization and signaling critically modulates affective pain and modality-specific pain hypersensitivity in chronic neuropathic pain.…”
mentioning
confidence: 99%